Factors associated with fear of falling and associated activity restriction in community-dwelling older adults: a systematic review - Denkinger, Michael D.; Lukas, Albert; Nikolaus, Thorsten; Hauer, Klaus (American journal of geriatric psychiatry, 2014)
Objective Fear of falling (FOF) is an important threat to autonomy. Current interventions to reduce FOF have yielded conflicting results. A possible reason for this discrepancy could be its multicausality. Some risk factors may not have been identified and addressed in recent studies. The last systematic review included studies until 2006. Methods To identify additional risk factors for FOF and to test those mentioned previously, we conducted a systematic literature review. Studies examining FOF in community-dwelling older adults between 2006 and October 2013 were screened. Results Outcomes are summarized with respect to different constructs such as FOF, fall-related self-efficacy/balance confidence, and FOF-related activity restriction. Odds ratios and p values are reported. There is no clear pattern with regard to the different FOF-related constructs studied. The only parameters robustly associated across all constructs were female gender, performance-based and questionnaire-based physical function, the use of a walking aid, and, less robust, a history of falls and poor self-rated health. Conflicting results were identified for depression and anxiety, multiple drugs, and psychotropic drugs. Other potentially modifiable risk factors were only mentioned in one or two studies and warrant further investigation. Parameters with mainly negative results are also presented. Conclusion Only few risk factors identified were robustly associated across all FOF-related constructs and should be included in future studies on FOF. Some newer factors have to be tested again in different cohorts. The comprehensive overview might assist in the conceptualization of future studies.
Kein PDF verfügbar
Gesehen am 06.11.2020